THE IMPORTANCE OF VOCABULARY WORK FOR LEARNING THE RUSSIAN LANGUAGE (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
The article examines the role of the dictionary in expanding the vocabulary of students in the process of learning Russian, studying various vocabulary words, their role in speech, as well as the ability to use them correctly in speech, tasks and optimal types of exercises that help to use them correctly. In addition to using traditional types of vocabulary work, ideas are also expressed about innovative ways to increase vocabulary, develop speech and broaden students' worldview.